Establishing an electronic breast cancer medical record module with automation for patient care and research: A clinical workflow based solution in University Malaya Medical Centre / Nurul Aqilah Mohd Nor - Nurul Aqilah , Mohd Nor (2019)
Advances in medical domain has led to an increase of clinical data production which offers enhancement opportunities in the clinical research sector. It is important for digital health technology to complement and fit into the existing clinical workflow in a single electronic medical record (EMR). In this study, we propose to expand the scope of EMR in the University Malaya Medical Centre (UMMC) using the Quality Implementation Framework (QIF) in establishing interoperability functions between clinical departments involving diagnosis, screening and treatment of breast cancer and building an automatic system for patient care, clinical audit and potential data mining to improve breast cancer outcomes. The completion of the i-Pesakit© Breast Cancer Module electronic structured clinical documentation complements the actual clinical workflow through data integration of clinical departments towards setting up a research-focused patient data governance model. The four main phases of QIF in this study are initial considerations about host setting, creating structure for implementation, ongoing structure during implementation, and future application improvement. The architectural framework module incorporates both clinical and research needs that comply to the Personal Data Protection Act. The output of i-Pesakit© Breast Cancer Module includes effective clinical data workflow management through an interoperable information technology and research focused governance model. This multidisciplinary collaboration enhanced the data capture quality in patientcare, benefited hospital data monitoring, quality assurance, iv registry reporting and research workflow suitable for a middle-income country setting. Future applications include establishing interoperability with other clinical departments, external organization such as the National Registration Department for mortality data, clinical audit for quality assurance and data mining for clinical research.